SAT0492 Prevalence of the metabolic syndrome in patients with systemic sclerosis. (12th June 2018) - Cuomo, G.; Danzo, F.; Masini, F.; Ferrara, R.; Pinotti, E.; Romano, C.; Adinolfi, L.E.
Abstract : Background: The metabolic syndrome is an independent risk factor for ischaemic heart disease. Patients with systemic lupus eriythematosus have un increased prevalence of the metabolic syndrome. 1 There are no controlled studies of the metabolic syndrome in patients with SSc. Objectives: To compare the prevalence of the metabolic syndrome in patients with SSc and controls and to evaluate its relationship to activity and severity of disease. Methods: Methods: 50 consecutive patients with SSc (45 female, median age 48; range 20–72) and 50 controls (patients whit fibromyalgia) (45 female, median age 46; range 25–72) were studied. The prevalence of the metabolic syndrome was compared in patients and controls using the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATPIII): central obesity: waist. 102 cm in men and. 88 cm in women; 2 hypertriglyceridaemia:>150 mg/dl; 3 low HDL, 40 mg/dl in men and, 50 mg/dl in women; 4 high blood pressure:>130/85 mm Hg or use of drugs for high blood pressure; and 5 high fasting glucose >110 mg/dl, and associations with activity and severity of the disease were examined. Results: The metabolic syndrome was present in 24% of patients and in 30% of controls subjects (p>0.05). Among patients with SSc, the metabolic syndrome was significantly associated with higher value of ESR (ESR >30) (5/7 vs 4/34;p=0.027). Neither disease activity nor severity scores were associated with the metabolic syndrome Conclusions: Patients with SSc have a lower prevalence of the NCEP-ATPIII-defined metabolic syndrome than controls. This result may help to justify the coronary prevalence in SSc patients similar to that of the general population. 2–3 References: [1] Bengtsson AA, et al. PLoS One2016Jul;21;11(7). [2] Hattema ME, et al. Rheumatology2008;45:578–83. [3] Akram MR, et al. Rheumatology2006;45:1395–8. Disclosure of Interest: None declared